The Perlindungan Kekerasan Pelecehan Terhadap Perempuan di Indonesia - Qotimah, Aulia Khusnul; Azizah, Ayu Nur; Nursherlyna, Nursherlyna (TIN: Terapan Informatika Nusantara, 2020)
Violence of sexual harassment against women is one of the serious problems faced in Indonesia. Therefore protection is needed for women who have been victims of human rights violations, namely women's rights, especially victims of sexual harassment. Sexual harassment is anything that forces sexual intercourse or intimacy or does any other action that is unwanted by the victim and is done forcefully on the victim. This action can affect psychological health, physical injury, and trauma to victims of sexual harassment. The purpose of this study is 1) to find out all the phenomena that occur in Indonesia against female harassment 2) To obtain solutions to cases of protection against female harassment in Indonesia. This research is a descriptive quantitative research